A novel recycling technology for chrome shavings: efficient separation of chromium and collagen fibers based on swelling inhibition in alkali-acid processing - Honghong Chen; Minghui Li; Sadaqat Ali Chattha; Xu Zhang; Biyu Peng; Chunxiao Zhang (Collagen and Leather)
Abstract Dechroming techniques with a low degree of collagen hydrolysis and a high degree of dechroming are more suitable for the resource utilization of chrome shavings. However, achieving efficient simultaneous separation of chromium and collagen fibers is challenging because swollen collagen fibers absorb a large amount of chromium-containing water and are prone to hydrolysis after dechroming. This study investigated the correlation between the swelling inhibition of collagen fibers and the extent of dechroming and optimized the process parameters. The results demonstrated that the incorporation of neutral salt significantly increased the rate of dechroming and reduced the degree of collagen hydrolysis. The optimized alkali-acid-washing process was as follows: soaking in a Na2SO4 solution (4%, w/w), dechroming with a NaOH solution at pH 13.5, rapidly adjusting the pH of reactants to 1.0 with an H2SO4 solution, pressure filtration, washing the filtered residue with 5% Na2SO4 solution (w/w) at pH 1.0, followed by pressure filtration. After two cycles of the alkali-acid-washing process, the filtered residue was washed with an oxalic acid-Na2SO4 solution (5%, w/w) and pressure-filtered again. The chromium content of recovered collagen was reduced to 34.0 mg/kg. The degree of collagen hydrolysis was confined to 9% with the fiber morphology completely retained. The wastewater chromium content was reduced to 0.4 mg/L after the simple precipitation, meeting the direct discharge requirement. The recycled chrome was utilized as chrome-tanning agent. These results suggested that the established method could be a promising resource reutilization route for the sustainable development of the leather industry. Graphical abstract